Evaluasi dan Perbaikan Antarmuka Aplikasi e-TPT KPP Pratama Malang Utara Menggunakan Pendekatan Human-Centered Design (HCD) - Arief Rino Wahyu Putra; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
KPP Pratama Malang Utara published the application of e-TPT KPP Pratama Malang Utara to improve the quality of office services to taxpayers. the e-TPT application was developed to facilitated the services and related to retrieving queue numbers, tracking files, online consultations, and information on requirements and petition. however, this application still had usability related problems reported by users, such as the save button in the settings when it doesn't work, and content that does not match with the title menu. The purpose of this study are evaluate and improve the e-TPT application interface with the Human-Centered Design (HCD) approach. HCD is an approach to developing interactive systems that aim to make the system useful by focusing users into the development process. hcd has four stages, the first stage are understanding and specifying the context of use, the results obtained at this stage are the characteristics of taxpayers. the second stage is specifying the user requirements, evaluating the application using the usability testing method which aims to identify usability problems in the application. Usability testing uses five aspects of Nielsen, it calls learnability, efficiency, memorability, errors, and, satisfaction. In the satisfaction aspect, the system usability scale questionnaire was used. The results of the initial evaluation of the learnability aspect had received 51.25%, efficiency aspects 46.22%, aspect errors 30.08%, memorability aspects in terms of time increased by 45% and in terms of number of tapes 39.2% from initial testing, and aspects of satisfaction 40,5%. The initial evaluation found 11 problems from observations, 14 problems from interviews, and combined with 9 problems. the third stage is producing design solutions, the results of this stage are information architecture, low-fidelity, high-fidelity, and prototypes to solve the problems in the previous stage. the last stage evaluating the design usability testing and sus questionnaire, and getting better results from the initial design. the results of the learnability aspects get 100%, efficiency 100%, errors 0%, memorability in terms of time increases 49.05% and the number of tap 20.7%, satisfaction 78%. Comparison of the results of the initial design and solution design is a design solution that has a better impact on the usability aspects of the user.